Chemical Components Analysis of Kencur (Kaempreria galanga L) Essential Oil Using GC-MS Method and Its Insecticide Tests on Fruit Fly (Bactrocera sp.) - Surbakti, Darwis; Simangunsong, Dedy Christopher (Journal of Chemical Natural Resources, 2023)
The hydrodistillation method isolated the essential oils of Kencur (Kaempreria galanga L) using the Stahl apparatus. It was distilled for Â± 5-6 hours to produce as much as 0.89% (w/w) essential oil. The chemical components of Kencur essential oil were analyzed using GC-MS, consisting of 7 compounds which seven compounds could be identified, name: Limonene (2.39%), Cineol (2.22%), and terpenes (0.80%). Hexane (1.51%), Borneol (13.23%), Methyl cinnamate (1.50%), ethyl ester (78.35%) and its insecticide test from Kencur essential oil showed Bactrocera sp. mortality. The highest was 96.7% in the 3% ginger rhizome essential oil concentration